Evaluation of image quality and assessability of a new flat-panel 3D C-arm compared to mobile and fixed computed tomography in posterior spinal fixation - Keil, Holger; Luxenhofer, Miriam; Vetter, Sven Y.; Beisemann, Nils; Grutzner, Paul A.; Franke, Jochen (International Journal of Medical Robotics and Computer Assisted Surgery, 2020)
Background This study evaluates image quality of a new flat-panel three-dimensional (3D) C-arm to the current generation and to intraoperative and stationary computed tomography (CT) in spinal surgery.
CRIS-Team WoS Importer:2020-11-20